KAJIAN POTENSI PENATAAN KAWASAN TERMINAL MANGKANG BERBASIS TRANSIT ORIENTED DEVELOPMENT (TOD) - Rizqy Ridho (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2023)
One of the transportation problems in big cities, one of which is Semarang City, which is congestion, this is proven by the growth of vehicles every year dominated by cars and motorbikes. This shows that public transport services are uneven, and not proportional to the rate of population growth that increases every year. Government efforts in overcoming these problems by planning the implementation of the Transit Oriented Development Concept (TOD). Budi Setyadi (in kompas.com 2018) as Director General of Land Transportation stated that type A terminals in Cirebon, Semarang, Solo, and Malang as pilot terminals were developed into TOD areas. The concept of TOD is a concept that emphasizes the creation of a regional or environmental center that plays a direct role as a transit point related to the formation or design of commercial areas and settlements to maximize access to transportation, especially the use of public transportation. The purpose of this research is to identify potential land uses and indications of policies based on weighting spatial variables from related stakeholders in the area around Terminal Mangkang Semarang to the concept of transit oriented development (TOD), so as to support sustainable development. In addition to integrating land use with the surrounding area, the role of stakeholders plays an important role. If there is no role of stakeholders, the provision of facilities and infrastructure in the implementation of the TOD concept will not be properly implemented and neglected. So that efforts are needed to explore indications that affect the community to choose TOD development.